Using Tangible User Interfaces (TUIs): Preliminary Evidence on Memory and Comprehension Skills in Children with Autism Spectrum Disorder - Mariagiovanna De Luca; Ciro Rosario Ilardi; Pasquale Dolce; Angelo Rega; Raffaele Di Fuccio; Franco Rubinacci; Maria Gallucci; Paola Marangolo (Behavioral Sciences)
Autism spectrum disorder (ASD) is a complex neurodevelopmental condition involving persistent challenges with social communication, as well as memory and language comprehension difficulties. This study investigated the effects of a storytelling paradigm on language comprehension and memory skills in children with ASD. A traditional approach, using an illustrated book to deliver the narrative, was compared to a novel paradigm based on Tangible User Interfaces (TUIs) combined with multisensory stimulation. A group of 28 children (ages between 6 and 10 years old) was asked to listen to a story over four weeks, two times a week, in two different experimental conditions. The experimental group (n = 14) engaged with the story using TUIs, while the control group (n = 14) interacted with a corresponding illustrated book. Pre- and post-intervention assessments were conducted using NEPSY-II subtests on language comprehension and memory. At the end of the intervention, a trend of improved performance was found. In particular, a greater number of subjects benefited from the intervention in the experimental group compared with the control group in instruction comprehension and narrative memory-cued recall. These preliminary findings suggest that TUIs may enhance learning outcomes for children with ASD, warranting further investigation into their potential benefits.